2003
DOI: 10.1590/s0102-311x2003000700015
|View full text |Cite
|
Sign up to set email alerts
|

Tendências no perfil nutricional das crianças nascidas em 1993 em Pelotas, Rio Grande do Sul, Brasil: análises longitudinais

Abstract: Trends in nutritional status were studied in children born in 1993 in the city of Pelotas, Rio Grande do Sul State, Brazil. During that year, all infants born in the city were identified, and a sub-sample of 1,273 children was visited twice at home for anthropometric examinations at an average age of 12 and 54 months, respectively. Approximately 10% of all children were lost to follow up from birth to 4 years. The prevalence of nutritional deficit decreased, while that of overweight increased between ages 1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
22

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 11 publications
3
11
0
22
Order By: Relevance
“…A comparação de duas coortes de nascimento em Pelotas (1982 e 1993), mostrou que a prevalência de obesidade teve um aumento de 40,0% no período de 11 anos, passando de 4,0% para 6,7%, em crianças com 12 meses de idade 8 . A prevalência de sobrepeso nas crianças dessas mesmas coortes quando foram acompanhadas aos quatro anos de idade dobrou, sendo próxima de 5,0% e 10,0% em 1986 e 1997, respectivamente 9 .…”
Section: Introductionunclassified
“…A comparação de duas coortes de nascimento em Pelotas (1982 e 1993), mostrou que a prevalência de obesidade teve um aumento de 40,0% no período de 11 anos, passando de 4,0% para 6,7%, em crianças com 12 meses de idade 8 . A prevalência de sobrepeso nas crianças dessas mesmas coortes quando foram acompanhadas aos quatro anos de idade dobrou, sendo próxima de 5,0% e 10,0% em 1986 e 1997, respectivamente 9 .…”
Section: Introductionunclassified
“…10,11 No Brasil, a situação não é diferente 5,12 , refletindo uma transição nutricional pela qual o país está passando e que exige intervenções nutricionais adequadas. 5,13 Este fato ganha relevância, pois indivíduos obesos na infância apresentam elevado risco de permanecerem obesos na vida adulta.…”
Section: Discussionunclassified
“…10,11 No Brasil, a situação não é diferente 5,12 , refletindo uma transição nutricional pela qual o país está passando e que exige intervenções nutricionais adequadas. 5,13 Este fato ganha relevância, pois indivíduos obesos na infância apresentam elevado risco de permanecerem obesos na vida adulta. 14 Os resultados do estudo apontam prevalência de excesso de peso de 27,8% na amostra analisada, sendo maior em relação ao estudo de Salomons et al 15 na cidade de Arapoti-PR, com crianças da rede Municipal de Ensino, que encontraram uma prevalência de 20,9% de excesso de peso.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…5 Gigante et al found a higher percentage of children with deficits in weight/age (W/A) and S/A indices at the end of their first year of life among those who had been born at LBW. 6 Notwithstanding, other variables, such as unfavorable socioeconomic conditions, early weaning and diarrhea also contribute to nutritional deficits, thereby interfering with interpretation of the association of birth weight with nutritional status in the form of confounding variables. 7 Childhood malnutrition, manifest by severely compromised linear growth and/or extreme emaciation, is one of the most serious problems in developing societies.…”
Section: Introductionmentioning
confidence: 99%